Media and Education Effect on Impaired Driving Associated With Alcohol Service. (December 2018) - George, Michael D.; Bodiford, Ashley; Humphries, Caroline; Stoneburner, Kristy A.; Holder, Harold D.
This study tested a three-component community prevention intervention with alcohol businesses to reduce alcohol overservice and to reduce drinking and driving crashes using a longitudinal design. The intervention involved a responsible beverage serving practices toolkit, a series of on-site visits from law enforcement, and a supporting media campaign. The effort achieved a reduction in the monthly percentage of drivers arrested for driving under the influence who cited the alcohol-licensed establishments as the place of last drink, and the number of establishments mentioned 2+ times as well as a decline in alcohol-involved crashes in the 12-month postintervention period. Results supported a conclusion that the intensive intervention media can achieve a reduction in the frequency with which drinking drivers utilized bars and restaurants and overall impaired driving-related crashes.